Pengenalan Konsep Media Ramah Anak Di Kelurahan Pancoran Mas, Kota Depok - Jati Satrio; Chairun Nisa Zempi; Dewanto Samodro (Universitas Persada Indonesia YAI, 2023)
Realizing the existence of child-friendly media is the first step in realizing inclusive media for everyone.This article looks at the problems that arise in sub-urban areas where the flow of information can pass with amassive volume and high speed. The emergence of alternative media, such as social media, has changed theway suburban people get information. This article tries to see the difference between press media and socialmedia, as the two main sources of information, in terms of realizing child-friendly media. This article alsounderlines the role that all elements of society can play in realizing child-friendly media in their respectiveenvironments.